Technical Efficiency and Return to Scale in The Indonesia Economy During The New Order and The Reformation Governments - Muchdie, Muchdie (Universitas Muhammdaiyah Surakarta, 2016)
This paper analyses technical efficiency and return to scale in the Indonesia economy during the year of 1967 to 2013. These range of years covering two eras of Indonesian government; the New Order era that lasted between the year of 1966 to 1998 and the Reformation era during the year 1998 to 2014. The analysis was also based on the Indonesia economyâs business cycle those categorised as Oil Booming Phase (1967-1981), Recession Phase (1982-1986), Deregulation Phase (1987-1996), Multidimension Crisis Phase (1997-2001) and Economic Recovery Phase (2002-1013). Using data on Gross Domestic Product based on constant price of the year 2000, capital stock with the same based year and employment (1967-2013), Cobb-Douglas production functions were exercised to calculate technical efficiency and Â return to scale employing regression analysis tehniques. The results show that technical effiency during the New Order Goverment were better than those during Reformation Goverment.